1990
DOI: 10.1016/0378-1097(90)90315-h
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the genes encoding the 51.4- and 41.9-kDa toxins of Bacillus sphaericus 2297 by deletion mutagenesis: the construction of fusion proteins

Abstract: A series of deletion mutants have been constructed, in which varying numbers of amino acids have been deleted from both the N- and C-termini of both the 51.4- and 41.9-kDa toxins of Bacillus sphaericus. The results show that between 34-39 and 52-54 amino acids respectively at the N- and C-termini of the 51.4-kDa protein, are not essential for toxicity. In the case of the 41.9-kDa protein, the removal of only 7 amino acids from the C-terminus abolishes toxicity whilst at least 17 amino acids can be deleted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 3 publications
6
20
0
Order By: Relevance
“…Consistent with previous results (Broadwell et al, 1990a, b; Davidson et al, 1990;Oei et al, 1990), when P51 or P42 were fed alone to larvae they were not toxic, even at a concentration of 250 pg ml-l . A combination of the two proteins was toxic to larvae, confirming that the C. Oei, J .…”
Section: Pur8cation and Cleavage Of The Fusion Proteinssupporting
confidence: 92%
“…Consistent with previous results (Broadwell et al, 1990a, b; Davidson et al, 1990;Oei et al, 1990), when P51 or P42 were fed alone to larvae they were not toxic, even at a concentration of 250 pg ml-l . A combination of the two proteins was toxic to larvae, confirming that the C. Oei, J .…”
Section: Pur8cation and Cleavage Of The Fusion Proteinssupporting
confidence: 92%
“…Consistent with the processing of the toxin, deletion experiments have shown that 17 amino acids can be removed from both the N-and C-terminus of BinA and that 34 residues can be removed from the N-terminus and 53 from the C-terminus of BinB, without abolishing toxicity (Broadwell et al, 1990b;Clark and Baumann, 1990;Oei et al, 1990).…”
Section: Bin Toxinsmentioning
confidence: 74%
“…The Bin toxin is composed of two polypeptides namely, BinA (Mr, 41.9 kDa) and BinB (Mr,51.4 kDa). Together these proteins are highly toxic to larvae of Culex (Broadwell et al, 1990;Oei et al, 1990;Nicolas et al, 1993). Comparison of the genome sequence of the mosquitocidal bacterium B. sphaericus C3-41 with other Bacillus species reveals that the bin genes are present only in a subset of B. sphaericus strains and these show high levels of similarity among different serotypes and isolates (Hu et al, 2008).…”
Section: Introductionmentioning
confidence: 96%